Iron‐sulfur glutaredoxin 2 protects oligodendrocytes against damage induced by nitric oxide release from activated microglia. Issue 9 (15th June 2017) - Lepka, Klaudia; Volbracht, Katrin; Bill, Eckhard; Schneider, Reiner; Rios, Natalia; Hildebrandt, Thomas; Ingwersen, Jens; Prozorovski, Timur; Lillig, Christopher Horst; van Horssen, Jack; Steinman, Lawrence; Hartung, Hans‐Peter; et al.
Abstract: Demyelinated brain lesions, a hallmark of autoimmune neuroinflammatory diseases like multiple sclerosis, result from oligodendroglial cell damage. Activated microglia are considered a major source of nitric oxide and subsequent peroxynitrite‐mediated damage of myelin. Here, we provide biochemical and biophysical evidence that the oxidoreductase glutaredoxin 2 inhibits peroxynitrite formation by transforming nitric oxide into dinitrosyl‐diglutathionyl‐iron‐complexes. Glutaredoxin 2 levels influence both survival rates of primary oligodendrocyte progenitor cells and preservation of myelin structure in cerebellar organotypic slice cultures challenged with activated microglia or nitric oxide donors. Of note, glutaredoxin 2‐mediated protection is not linked to its enzymatic activity as oxidoreductase, but to the disassembly of its uniquely coordinated iron‐sulfur cluster using glutathione as non‐protein ligand. The protective effect of glutaredoxin 2 is connected to decreased protein carbonylation and nitration. In line, brain lesions of mice suffering from experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis, show decreased glutaredoxin 2 expression and increased nitrotyrosine formation indicating that this type of protection is missing in the inflamed central nervous system. Our findings link inorganic biochemistry to neuroinflammation and identify glutaredoxin 2 as a protective factor against neuroinflammation‐mediated myelin damage. Thus, improved availability of glutathione‐coordinated iron‐sulfur clusters emerges as a potential therapeutic approach in inflammatory demyelination. Main Points: Unique FeS protein Grx2 inhibits damage of myelin and oligodendrocyte progenitor cells induced by NO. FeS disassembly allows formation of dinitrosyl‐diglutathionyl‐iron‐complexes and prevents ONOO‐ formation and subsequent oxidative damage.